2004
DOI: 10.3354/meps266255
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of suspended solids on gill structure, osmoregulation, growth, and triiodothyronine in juvenile green grouper Epinephelus coioides

Abstract: Despite suspended solids being an important water-quality parameter in the regulatory process, very little is known about the risks of prolonged exposure to high concentrations of suspended solids in fish, especially marine species. In this study, the green grouper Epinephelus coioides, an important mariculture species with a wide geographic distribution, was exposed to various concentrations (0, 50, 100, 200, 1000 and 2000 mg l -1 ) of suspended solids for 6 wk. The results showed that exposure was not lethal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 24 publications
1
63
0
1
Order By: Relevance
“…Hughes and Morgan [102] found a thickening of the gill epithelium in fish acutely exposed to high levels of suspended solids that was responsible for fusion of the adjacent lamella. In green grouper (Epinephelus coioides) exposed to various concentrations (0, 50, 100, 200, 1000 and 2000 mg·L −1 ) of suspended solids for 6 weeks, Au et al [104] found nonlethal effects at environmentally realistic concentrations; however, they did find damage to the gill structure, such as epithelium lifting, hyperplasia in the pillar system, and reduction of epithelial volume. Clear signs of osmoregulatory stress have also been noted [102].…”
Section: Wastes and Faecesmentioning
confidence: 94%
See 1 more Smart Citation
“…Hughes and Morgan [102] found a thickening of the gill epithelium in fish acutely exposed to high levels of suspended solids that was responsible for fusion of the adjacent lamella. In green grouper (Epinephelus coioides) exposed to various concentrations (0, 50, 100, 200, 1000 and 2000 mg·L −1 ) of suspended solids for 6 weeks, Au et al [104] found nonlethal effects at environmentally realistic concentrations; however, they did find damage to the gill structure, such as epithelium lifting, hyperplasia in the pillar system, and reduction of epithelial volume. Clear signs of osmoregulatory stress have also been noted [102].…”
Section: Wastes and Faecesmentioning
confidence: 94%
“…According to Wilber and Clarke [107], fish species with a 24-h lethal concentration 10% (LC 10 ) value at an SS concentration <10,000 mg·L −1 are classified as sensitive. Unfortunately, as highlighted by Au et al [104], very little information is available about the effects of high concentrations of suspended solids for extended periods on fish health, and the knowledge for non-salmonids or fish is until now very limited.…”
Section: Wastes and Faecesmentioning
confidence: 99%
“…Areas subject to high sediment loads have a tendency towards higher turf algae cover, and potentially altered stable states dominated by sediment-trapping turfing algae (Airoldi and Cinelli, 1997;Airoldi, 2003;Bellwood and Fulton, 2008 The effects of sedimentation include mortality from smothering, behavioral modification, food limitation, and reduced growth rates, recruitment, and fertilization success across a wide range of marine vertebrate and invertebrate organisms (Babcock and Davies, 1991;Gilmour, 1999;Ellis et al, 2002;Airoldi, 2003;Au et al, 2004;Galbraith et al, 2006;Steger and Gardner, 2007;Chew et al, 2013;Halpern et al, 2013). For earlier vertebrate and invertebrate life stages, increased suspended sediment has led to reduced hatching success, larval survival and settlement, and increased abnormal larval development and mortality (Auld and Schubel, 1978;Babcock and Davies, 1991;Gilmour, 1999;Griffin et al, 2009;Wenger et al, 2011;McLaughlin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Short-term or episodic sediment exposure events are more consistent with the temporal patterns of sediment exposure associated with in-stream construction activity than are more chronic periods of exposure as discussed above. Au et al (2004) studied the responses of coastal green grouper to suspended sediment concentrations between 0 and 2,000 mg l −1 over a period of 6 weeks. The authors found that elevated suspended sediment concentrations did not affect food consumption or growth; however, increased sediment-loading did cause gill damage and increase osmoregulatory and physiological stress.…”
Section: Fishmentioning
confidence: 99%